2014
DOI: 10.1177/0954407014547930
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a lane change on a car-following manoeuvre: anticipation and relaxation behaviour

Abstract: Car-following and lane-changing manoeuvres are the most common driving behaviour on urban roads and highways. Although these two manoeuvres have been studied extensively, the effect of a lane change on a car-following manoeuvre remains elusive. Analysing these effects leads to integration of the car-following and the lane-changing manoeuvre which has been relatively neglected. A lane-changing manoeuvre causes the immediately following driver to deviate from common car-following models to accommodate the lane c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…For instance, Zheng et al (2013) found that a follower undergoes three stages during a lane-changing manoeuvre: (a) anticipation (the change in driving behaviour of the follower when s/he notices the lane-changing request), (b) relaxation (where the follower and its leader are willing to accept a shorter spacing and then relax to normal spacing), and (c) change in the follower's behaviour (an aggressive (timid) driver becomes less aggressive (timid)). Similar observations have been reported by other researchers (Ghaffari et al, 2015, Li et al, 2018. These studies only consider the case where the follower is assumed to yield (or show courtesy) to a successful lane-changing manoeuvre, however, past research suggests that followers may try to avoid a lane-changing request by accelerating and closing down the lag gap (Hidas, 2002, Talebpour et al, 2015, Kang and Rakha, 2017, Ali et al, 2019b.…”
Section: Drivers' Responses To Lane-changingsupporting
confidence: 78%
“…For instance, Zheng et al (2013) found that a follower undergoes three stages during a lane-changing manoeuvre: (a) anticipation (the change in driving behaviour of the follower when s/he notices the lane-changing request), (b) relaxation (where the follower and its leader are willing to accept a shorter spacing and then relax to normal spacing), and (c) change in the follower's behaviour (an aggressive (timid) driver becomes less aggressive (timid)). Similar observations have been reported by other researchers (Ghaffari et al, 2015, Li et al, 2018. These studies only consider the case where the follower is assumed to yield (or show courtesy) to a successful lane-changing manoeuvre, however, past research suggests that followers may try to avoid a lane-changing request by accelerating and closing down the lag gap (Hidas, 2002, Talebpour et al, 2015, Kang and Rakha, 2017, Ali et al, 2019b.…”
Section: Drivers' Responses To Lane-changingsupporting
confidence: 78%
“…One of these methods is to employ Moving Average Filter. 27,28 This method calculates the average of data before and after a point in time. Moving Average Filter (window size 9) is utilized in the present research.…”
Section: Hypotheses and A New Idea In The Determination Of Initial Anmentioning
confidence: 99%
“…The model of LC was classified as a mandatory lane change (MLC) or a discretionary lane change (DLC) [12]. MLC, it occurs when a driver is obliged to leave the lane or change the lane in order to reach his/her destination, for example, to use an off-ramp [13].…”
Section: Lane Changing Modelsmentioning
confidence: 99%